Tumor necrosis factor‐alpha inhibits differentiation of myogenic cells in human urethral rhabdosphincter. (22nd March 2017) - Shinohara, Mayuka; Sumino, Yasuhiro; Sato, Fuminori; Kiyono, Tohru; Hashimoto, Naohiro; Mimata, Hiromitsu
Abstract : Objectives: To examine the inhibitory effects of tumor necrosis factor‐α on myogenic differentiation of human urethral rhabdosphincter cells. Methods: A rhabdosphincter sample was obtained from a patient who underwent total cystectomy. To expand the lifespan of the primary cultured cells, rhabdosphincter myogenic cells were immortalized with mutated cyclin‐dependent kinase 4, cyclin D1 and telomerase. The differential potential of the cells was investigated. The transfected human rhabdosphincter cells were induced for myogenic differentiation with recombinant human tumor necrosis factor‐α and/or the tumor necrosis factor‐α antagonist etanercept at different concentrations, and activation of signaling pathways was monitored. Results: Human rhabdosphincter cells were selectively cultured for at least 40 passages. Molecular analysis confirmed the expression of myosin heavy chain, which is a specific marker of differentiated muscle cells, significantly increased after differentiation induction. Although tumor necrosis factor‐α treatment reduced the myosin heavy chain expression in a concentration‐dependent manner, etanercept inhibited this suppression. Tumor necrosis factor‐α suppressed phosphorylation of protein kinase B and p38, whereas etanercept pretreatment promoted phosphorylation and myosin heavy chain expression in a concentration‐dependent manner. Conclusions: Tumor necrosis factor‐α inhibits differentiation of urethral rhabdosphincter cells in part through the p38 mitogen‐activated protein kinase and phosphoinositide 3‐kinase pathways. Inhibition of tumor necrosis factor‐α might be a useful strategy to treat stress urinary incontinence.